Paediatric norms for photopic electroretinogram testing based on a large cohort of Chinese preschool children - Henry Ho-lung Chan; Sonia Seen-hang Chan; Kai Yip Choi (BMJ Open Ophthalmology)
Objective Full-field electroretinogram (ffERG) is an objective test to determine the electroretinal activities in response to light stimulation for investigating retinal physiology and diagnosing retinal diseases. This study aimed to establish a reference data set of photopic electroretinogram (ERG) of Chinese preschool children in Hong Kong to facilitate clinical and research studies.Methods and analysis Preschool children aged 3–7 years with normal vision were recruited from local kindergartens. Eye examinations, including cycloplegic spherical equivalent refraction (SER), axial length (AL) and keratometry (K) measurements, were performed. ffERGs of the International Society for Clinical Electrophysiology of Vision (ISCEV) standard photopic flash and 30-Hz flicker protocols were measured using RETeval with Sensor Strip skin electrodes. ERG waveform characteristics were extracted, and relationships between ERG, age, SER, AL and K were evaluated.Results A total of 479 children completed the measurements (mean age: 5.0±0.9 years, 45.5% female). Mean, 95% CIs, 5th–95th percentile range of the ERG parameters were reported. Age was positively associated with amplitudes of b-wave and 30-Hz flicker (p<0.01), but negatively associated with implicit times of b-wave and 30-Hz flicker (p<0.01). AL was significantly associated with all amplitudes of a-wave, b-wave and 30-Hz flicker (p≤0.01) and implicit time of both a-wave and 30-Hz flicker (p<0.05). K was positively associated only with 30-Hz flicker amplitude (p=0.01), and no association between all responses and SER.Conclusion Reference data set of photopic ERG of Chinese preschool children was established. Cross-sectional investigations revealed associations between ERG, age, SER and AL, which were speculated to further implicate the role of retina in refractive error development.